Molecular evidence of Borrelia burgdorferi sensu lato in patients in Brazilian central-western region - Lopes, Fernando Aguilar; Rezende, Jania de; Santos Silva, Danielly Beraldo dos [UNESP]; Goncalves Alves, Fernanda de Cassia; Oliveira, Carina Elisei de; Costa, Izaias Pereira da (Elsevier B.V., 2017)
We aimed to detect DNA of Borrelia burgdorferi in whole blood and serum samples of patients with clinical symptoms and epidemiology compatible with Brazilian Lyme-like disease. Four patients with positive epidemiological histories were recruited for the study. Blood samples were collected, screened by serologic testing by ELISA and Western blotting and molecular identification of B. burgdorferi by amplifying a fragment of the conserved gene that synthesizes the hook flagellar flgE. The results showed positive serology and for the first time, the presence of B. burgdorferi sensu lato in humans in the Midwest region of Brazil. The resulting sequences were similar to GenBank corresponding sequences of B. burgdorferi flgE gene. By neighbor-joining the phylogenetic analysis, the flgE sequence of the Brazilian strain clustered in a monophyletic group with the sequence of B. burgdorferi sensu lato under 100% bootstrap support. This study opens up promising perspectives and reinforces the need for additional studies to determine the epidemiological characteristics of the disease, as well as the impact of the prevalence of Brazilian borreliosis in Mato Grosso do Sul State, Brazil. (C) 2017 Elsevier Editora Ltda.
Keywords: Borrelia burgdorferi; Lyme disease; flgE; Baggio-Yoshinari syndrome; Brazil